(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2017)
This article offers an analysis of one small-nation market’s perspective on the current and expected changes of digital distribution and its intermediaries. It demonstrates how key stakeholders in the Czech audiovisual distribution sector are reacting to regulatory processes at the EU level and how they are reconsidering their existing business practices, strategic plans, and structural positions vis-à-vis new global trends and competition in the evolving sphere of digital distribution. The article is not a full- edged analysis of the Digital Single Market’s (DSM) potential impacts: instead, it considers DSM as just one factor in the strategic thinking of stakeholders, a factor that functions as a catalyst and a focal point in both business operations and policy-making.